The Syriac Orphanage and School in Beirut: Building an Elite Transnational Syriac Identity - Hager, Anna (Studies in world christianity, 2022)
Despite a growing interest in Middle Eastern Christianity, an imbalance persists in scholarly understanding of individual Christian communities. The Syriac Orthodox – a non-Catholic Oriental Orthodox community – are one such understudied group. After experiencing massacres during World War I, they resettled in Lebanon, Syria, Iraq and Palestine, which were then newly established nation-states. This article is concerned with the Syriac school in Beirut (also called the Assyrian Orphanage and School) as a case study of the Syriac Orthodox effort to both revive the community and produce an elite that would succeed in a largely non-Syriac, Arabic environment. The school was first founded in 1919 in Adana, Cilicia, in today’s south-eastern Turkey, which was then under French occupation. In 1923 it resettled in Beirut. For several decades it was one of the few, if not the only, successful Syriac Orthodox school in the Middle East. But from the outset it faced an inherent contradiction: despite its focus on the Syriac language, its success was dependent on the graduates’ ability to thrive in a largely non-Syriac, Arab, and in our case, Lebanese, environment. I argue that it was precisely this exclusively defined Syriac identity which enabled their entry into the larger, transnational environment in which national identities were still being negotiated. This article, which is part of a project on the Syriac Orthodox in Lebanon, draws on sources in Arabic, French, English and Syriac from both inside and outside the community (such as the French archives).1